Do eucalypt plantations on Ferrosols in north-west Tasmania contain more or less soil carbon than native forests on the same soil type?. Issue 2 (3rd April 2022) - McIntosh, P. D.; Slee, A. J.; Thomson, R.
ABSTRACT: Although studies in mainland states of Australia and overseas show that the conversion of native forests to plantations can reduce carbon (C) stocks in soils, no studies have been undertaken in Tasmania to assess how plantations affect soil C stocks. To address this knowledge gap, we compared soil C concentrations and C stocks to 30 cm depth in native 'mixed' eucalypt forests and adjacent Eucalyptus nitens plantations on Ferrosols in north-west Tasmania, using a factorial sampling strategy. Mean soil C and nitrogen (N) concentrations were significantly lower in plantations than in mixed forests; however, because the soils in plantations had higher bulk density, mean soil C stocks under the two treatments (114 Mg ha −1 and 116 Mg ha −1, respectively) were not significantly different. It is concluded that machine removal of 5–6 cm of topsoil into windrows during land clearing for plantations would be sufficient to explain why C concentrations were lower in plantations than in mixed forests and that, apart from this physical effect of land preparation, 17–21 years of plantation growth on Ferrosols in north-west Tasmania has not significantly affected soil C stocks in mineral soil. This result can be partly explained by the ability of Ferrosols to form stable complexes between organic matter, sesquioxides and clays.